Utilisation Of Chicken Marination Using Turmeric Powder To Vantura Digital Agensi Employees - Harvey Febrianta; Dave Mangindaan (International Journal Of Community Service, 2025)
Limited time to process food is one of the challenges for Vantura Digital Agensi employees, especially because their activities with busy working hours, so it is necessary to conduct socialisation activities on the use of chicken meat products that are easy to process and nutritious. One of the training programmes that can be carried out is the use of chicken meat by marinating using turmeric powder. Besides being practical to do, the meat marination technique is able to increase the nutritional content and shelf life of the meat. The method used consists of the preparation stage to identify the background of the problem, planning activities, including licensing, up to the implementation stage. The results of this training activity are in the form of innovative chicken marinated products, some of which are packaged and stored at freezing temperatures, and some chicken marinated products that are directly cooked.  The socialisation of the use of chicken meat by mixing turmeric powder as a marination ingredient is expected to increase knowledge and skills regarding practical and nutritious chicken meat processing methods.